Development of K-Visual GKT Module for Improving Visualization Skill Based on The Art of Origami for Technical Drawing Subjects - Mohd Salehudin Marji; Aade Hatib Musta’amal; Lokman Mohd Tahir; Noraini Shaharudin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
Visualization skill is essential abbilites for every students who learn technical drawing, and mathematics in general. This skill could be improved through practical learning. K-Visual GKT designed to enhance students’ visualization skills through activities involving the art of origami and kirigami. This module, based on the Sidek Module Development Model, integrates origami and krigami to engage students in producing 3D paper folds independently. This paper will examine the validity and realibility of the module. This research conducted quantitatively and involves expert and students. The data collected will be analysis. The findings showed that the modules produced high validity values from experts (88%) and high reliability from all students (α=.846). The results affirm the effectiveness of the K-Visual GKT Module in enhancing students' visualization skills, providing a promising solution to address challenges in technical drawing education. Further examination of the module's potential impact on students' visualization skills is proposed, contributing to the ongoing efforts to improve visualization skills.